The Schadenfreude Effect: When Your Losses Are More Enjoyable Than My Wins (Revista Interdisciplinar de Marketing, 2018)
It is not uncommon for people to feel good when bad luck happens to others, especially when there is rivalry. The paper aims to investigate the impact of schadenfreude (pleasure in another’s misfortune) on decision-making. The first study, a lab experiment, showed that people preferred to send news about one’s favorite team victory (pride) over one’s rival team loss (schadenfreude) when the outcome of the game displayed small score differences and select the schadenfreude option when the score differences were large.  The second study, conducted in the field, showed that supporters of a rival team increased their probability of betting against the target team when the target team was praised prior to the game. Taken together, the results show that schadenfreude is more powerful when the damage to a rival is large (study 1) or when the rival is praised (study 2).